Implementasi Nilai-Nilai Karakter dalam Kurikulum Merdeka Pada Pembelajaran Pendidikan Agama Islam - Giyono, Amrul; Muslihun; Rusydi, Ibnu (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This research examines the implementation of character values in the Independent Curriculum of Islamic Religious Education (PAI) learning at SDN 7 Gianyar, Bali Province. The character values implemented include tolerance, national spirit, love of peace, love of reading, and responsibility. These values are instilled using an eclectic approach, combining the theories of habituation, sustainability, and change. Implementation involves making character values part of PAI learning evaluation materials and techniques. The research results show that the implementation of character values has a positive impact, including (1) building good, harmonious, and peaceful relationships between students of different religions at school; (2) increasing school achievement; and (3) decreasing levels of violence or bullying among students. This implementation succeeded in forming students with noble character according to Islamic teachings and creating harmony amidst cultural and religious diversity. This research contributes to developing religious-based character education in schools to realize peace and national unity.